Replacing protein via enteral nutrition in a stepwise approach in critically ill patients: the REPLENISH randomized clinical trial protocol - Yaseen M. Arabi; Hasan M. Al-Dorzi; Musharaf Sadat; Dina Muharib; Haifa Algethamy; Fahad Al-Hameed; Ahmed Mady; Adnan AlGhamdi; Ghaleb. A. Almekhlafi; Abdulrahman A. Al-Fares; Ayman Kharaba; Ali Al Bshabshe; et al. (Trials, 2023)
Abstract Background Protein intake is recommended in critically ill patients to mitigate the negative effects of critical illness-induced catabolism and muscle wasting. However, the optimal dose of enteral protein remains unknown. We hypothesize that supplemental enteral protein (1.2 g/kg/day) added to standard enteral nutrition formula to achieve high amount of enteral protein (range 2–2.4 g/kg/day) given from ICU day 5 until ICU discharge or ICU day 90 as compared to no supplemental enteral protein to achieve moderate amount enteral protein (0.8–1.2 g/kg/day) would reduce all-cause 90-day mortality in adult critically ill mechanically ventilated patients. Methods The REPLENISH (Replacing Protein Via Enteral Nutrition in a Stepwise Approach in Critically Ill Patients) trial is an open-label, multicenter randomized clinical trial. Patients will be randomized to the supplemental protein group or the control group. Patients in both groups will receive the primary enteral formula as per the treating team, which includes a maximum protein 1.2 g/kg/day. The supplemental protein group will receive, in addition, supplemental protein at 1.2 g/kg/day starting the fifth ICU day. The control group will receive the primary formula without supplemental protein. The primary outcome is 90-day all-cause mortality. Other outcomes include functional and quality of life assessments at 90 days. The trial will enroll 2502 patients. Discussion The study has been initiated in September 2021. Interim analysis is planned at one third and two thirds of the target sample size. The study is expected to be completed by the end of 2025. Trial registration ClinicalTrials.gov Identifier: NCT04475666 . Registered on July 17, 2020.